Error revising of blade tip-timing parameter identification caused by frequency sweep rate. (30th September 2022) - Zhi, Fengyao; Duan, Fajie; Liu, Meiru; Niu, Guangyue; Jiao, Jiangkun; Deng, Zhenyu; Jiang, Jiajia; Fu, Xiao
Highlights: The parameter identification errors under different frequency sweep rates are analyzed by frequency sweep parameter. An improved single-parameter method to reduce identification errors is proposed. A revised method to reduce identification errors of single-parameter method is proposed. The relative errors of peak amplitude and frequency are reduced to 1/7 and 1/8. Abstract: Blade tip-timing (BTT) is a rotating blade vibration measurement technology. It is a universal and effective method to acquire blade tip displacement data by frequency sweep and identify vibration parameters by single-parameter method. However, when the frequency sweep rate is too large, the vibration parameters obtained by single-parameter method will have large errors because the transient response cannot be immediately attenuated. For this problem, a dimensionless frequency sweep parameter is introduced, and two methods are proposed in this paper. When the engine order is known, an improved single-parameter method is proposed. For the unknown engine order, a revised method of vibration parameters is proposed. The effectiveness of the proposed two methods has been verified by simulation and experiment data. The results showed that when the frequency sweep parameter is between 0.3 and 15, the improved method and the revised method both significantly improve the vibration parameter identification accuracy.